Trapped in clichés: masculinity, films and tourism in Iceland. Issue 9 (2nd September 2017) - Loftsdóttir, Kristín; Kjartansdóttir, Katla; Lund, Katrín Anna
Abstract: When the Icelandic television series 'Trapped' was aired it instantly garnered worldwide attention. The main character, a rugged Icelandic man, is presented as being one with the harsh cold landscape. This article demonstrates how visual materials, like 'Trapped, ' have become extremely important in the presentation of Iceland to the outside world, as well as working to present Iceland as a tourism destination. Furthermore, we evidence how 'Trapped' identifies with the Nordic noir genre. Our analysis shows that the series 'Trapped' and recent Icelandic films rest on the strong and entrenched association of Icelandicness with maleness, while also reflecting on existing stereotypes about Iceland and the Icelandic people as being exotic, both of which have become reanimated through the tourism industry. Thus, visual material such as 'Trapped' constitutes a part of, and becomes in and of itself symbolic of recurrent masculinity in Iceland. Our analysis emphasizes the importance of framing the 'official' production of locations as tourism destinations by both state and commercial industries in relation to other cultural productions that often also engage with mobile historical stereotyping and commercial attempts at nation branding.